Community Participation and Development Planning in Local Governments in South-Western Uganda: A Case of Nyarushanje Sub-County Rukungiri District. - Ainembabazi, Tricia (Kabale University, 2024)
Community participation involves the engagement of local community members, groups, and organizations in planning and implementing development projects that affect their lives and well-being. In the context of development planning, this participation includes involving community members in decision-making to identify their needs, priorities, and preferences, ensuring these are reflected in development projects. However, the relationship between community participation and development planning remains unclear. This study aimed to investigate community participation and development planning in Nyarushanje Sub-county, Rukungiri District Local Government, Uganda. The specific objectives were to examine the state of community participation, assess the determinants and challenges of community participation, and identify possible solutions to these challenges. The study employed a mixed-methods approach, incorporating both qualitative and quantitative data. Qualitative data was open-ended, without predetermined responses, while quantitative data included closed-ended responses, as found in questionnaires. The mixed-methods approach facilitated the systematic convergence of qualitative and quantitative data, integrating different research designs. The findings suggest that community participation is crucial in the development planning process, enhancing community ownership and promoting project sustainability. Additionally, the study highlights the need for increased capacity building among community members and local government officials to facilitate effective participation and collaboration in development planning. The study concludes a significant relationship between community participation and development planning in Nyarushanje Sub-county, Rukungiri District. Key recommendations include: ensuring community involvement throughout the development planning sessions to foster a sense of ownership; adopting strategic planning for specific projects rather than attempting to address all community concerns at once; and, conducting community sensitization to improve understanding of ongoing projects and their benefits.